2007
DOI: 10.2224/sbp.2007.35.10.1323
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Personality Traits and Attending a Fitness Center

Abstract: The sports and recreation industry is emerging in Taiwan. Few related studies have used it as a sample. This study has been designed to explore the notion of personality traits based on fitness center members in Taiwan. Because of its validity and wide use (Furnham, Moutafi, & Crump, 2003), the Five Factor Model (FFM) developed by McCrae and John (1992) is adopted in this study to assess the personality of fitness center members. The measurement scale of personality traits is cited from Saucier's (1994) M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…According to the findings, extraverted people participate in many leisure activities very intensely and choose more adventurous and intense activities than introverts (Kovacs, 2007). Researchers have also found that extraverts prefer social activities more than their introverted counterparts (Argyle & Lu, 1990) and personality traits of extraversion are significantly related to greater overall leisure participation (Chen, Lee, & Chang, 2007;Kovacs, 2007;Lu & Hu, 2005;Lu & Kao, 2009;Tok, 2011). In the case of the neuroticism trait, some studies (Kovacs, 2007;Lu & Hu, 2005;Tok, 2011) suggested that it was negatively associated with leisure involvement.…”
Section: Discussionmentioning
confidence: 99%
“…According to the findings, extraverted people participate in many leisure activities very intensely and choose more adventurous and intense activities than introverts (Kovacs, 2007). Researchers have also found that extraverts prefer social activities more than their introverted counterparts (Argyle & Lu, 1990) and personality traits of extraversion are significantly related to greater overall leisure participation (Chen, Lee, & Chang, 2007;Kovacs, 2007;Lu & Hu, 2005;Lu & Kao, 2009;Tok, 2011). In the case of the neuroticism trait, some studies (Kovacs, 2007;Lu & Hu, 2005;Tok, 2011) suggested that it was negatively associated with leisure involvement.…”
Section: Discussionmentioning
confidence: 99%